Representations of Female Identity in Jasmile Zbanić's and Aide Begić's Films (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article explores figures of women as portrayed in four films by female directors Jasmila Žbanić and Aida Begić. These figures are examined in terms of identity formation against the backdrop of complex processes of social change that have occurred in Bosna and Hercegovina in the course of the last two decades. The films show women who mainly find themselves not only in the midst of severe social circumstances, but also under the sign of significant cultural change such as the rising of religious sources of influence. These films discuss different models of gender relationships through a female psychology within the context of gender roles in the former Yugoslavia as well as within more recent globalization contexts. The article explores the aforementioned topics within their given historical and religious frameworks as well as in terms of generational, social and gender relationships. While a few of the figures – including severely traumatized women and pubescent girls – are oriented towards the past, the majority of them look at the future, search for new roles and test new models of female identity. The films encourage strong and authentic women and do not facilitate models of self-victimization.
Keywords: gender relationship; female identity; post-Yugoslav films; female film directors